The Mediating Effect of Innovation on the Relationship Between Corporate Governance and Firm Performance: Evidence from Developed and Developing Countries - Ploypailin Kijkasiwat; Anwar Hussain; Uzma Nisar; Chee Yoong Liew (Asian Academy of Management Journal, 2024)
Prior studies have shown that innovation has a mediating effect on the relationship between corporate governance and firm performance. This study compares this mediating effect in developed and developing countries using agency theory and signaling theory. A panel sample of 2,688 firms in developing and developed countries is analysed for the period of 2002–2017. The empirical findings demonstrate that corporate innovation fully mediates the relationship between corporate governance and firm performance in developed countries. However, innovation partially mediates the relationship between corporate governance and firm performance in developing countries. This could be because of different socioeconomic factors and capabilities of innovators involved in corporate governance structure. The study has both theoretical and policy implications and provides insights for policy makers for identifying the influence of innovation on firm value and evaluating the importance of corporate governance.